Hematologic changes in experimentally induced feline steatitis: A comparative study between the Domestic shorthair and Siamese breed - KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F.; FYTIANOU (Α. ΦΥΤΙΑΝΟΥ), A.; KRITSEPI (Μ. ΚΡΙΤΣΕΠΗ), M.; MYLONAKIS (Μ.Μ. ΜΥΛΩΝΑΚΗΣ), M. M. (Journal of the Hellenic Veterinary Medical Society, 2018)
In order to study the hematological abnormalities in feline steatitis 10 Domestic shorthair (DSH) and 10 Siamese 2 to 3 month-old kittens were used to whom cooked sardines supplemented with minerals and vitamins, except vitamin E, were given for 4 consecutive months (experimental groups). An equal number of age and sex matched kittens for each breed that were being fed a commercial canned cat food based on oily fish and for the same period of time served as controls. Blood samples were taken at 0 time and at 15-day intervals thereafter for a CBC. Red and white blood cell morphology was also studied. Steatitis was reproduced in all the 20 kittens of the experimental groups. Five DSH kittens developed the clinical and 5 the subclinical form of the disease. The relevant figures for the affected Siamese kittens were 6 and 4, respectively. The clinical disease was significantly more severe in the DSH breed only at the very beginning of the experimental period (time 1). None of the controls belonging to both breeds developed clinical signs or lesions associated with steatitis. Low PCV(<25%) and decreased Hb concentration (<8 g/100ml) indicating anemia, and appearing as early as time 1, in the experimental groups were significantly more severe in the Siamese than in the DSH breed. Evidently the anemia was non-regenerative attributable to chronic inflammatory nature of steatitis. In most of the observation times significant neutrophilic leucocytosis was detected only in the experimental groups; a regenerative left shift was seen in approximatery 50% of all the cases with neutrophilia. Eosinophilia and monocytosis were of minor significance for both breeds. No erythrocyte and leucocyte morphological abnormalities were seen in the DSH or the Siamese experimental groups all over the experimental period.